Ozone and Ozone By-Products in the Cabins of Commercial Aircraft - Weisel, Clifford (2013)
The aircraft cabin represents a unique indoor environment due to its high surface-to-volume ratio, high occupant density and the potential for high ozone concentrations at cruising altitudes. Ozone was continuously measured and air was sampled on sorbent traps, targeting carbonyl compounds, on 52 transcontinental U.S. or international flights between 2008 and 2010. The sampling was predominantly on planes that did not have ozone scrubbers (catalytic converters). Peak ozone levels on aircraft without catalytic convertors exceeded 100 ppb, with some flights having periods of more than an hour when the ozone levels were > 75ppb. Ozone was greatly reduced on relatively new aircraft with catalytic convertors, but ozone levels on two flights whose aircraft had older convertors were similar to those on planes without catalytic convertors. Hexanal, heptanal, octanal, nonanal, decanal and 6-methyl-5-hepten-2-one (6-MHO) were detected in the aircraft cabin at sub- to low ppb levels. Linear regression models that included the log transformed mean ozone concentration, percent occupancy and plane type were statistically significant and explained between 18 and 25% of the variance in the mixing ratio of these carbonyls. Occupancy was also a significant factor for 6-MHO, but not the linear aldehydes, consistent with 6-MHO’s formation from the reaction between ozone and squalene, which is present in human skin oils.